Virtual Reality Training Improves Upper Limb Functions in Stroke Survivors: Virtual Reality Training and Upper Limb Function - Shahzadi, Namal; Ashar Rafi , Muhammad; Ishtiaq (Late), Komal; Ahmad, Naveed; Nawaz Malik, Arshad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Stroke survivors with upper extremity functional limitation are particularly susceptible to problems in performing independent ADLs. Virtual Reality training has a significant contribution to enhancing the independence of stroke survivors. Objective: To determine the effect of additional VR training on upper limb gross motor function, gross manual dexterity, and functional activities in hemiplegic stroke survivors. Methods: It was a single-group experimental study in which 20 participants were recruited through non-probability convenient sampling. Participants were included in the study if they had any sort of stroke (hemorrhagic or infarct), were between the ages of 30 and 70, had at least one score on the box and block test, and did not have any cognitive deficits or uncontrolled high blood pressure. The intervention was provided three days a week for a total of six weeks. Gross motor function, gross manual dexterity, and functional capacities of the upper limb were measured at baseline, 2nd, 4th and at 6th week of intervention through Fugl-Meyer Assessment, Box and Block Test, and Wolf Motor Assessment Scale respectively. Data were analyzed through within-group inferential analysis using SPSS-21 software. Results: The mean age of patients was 49.45 ± 11.02 years. The scores of the Fugl-Mayer Assessment Scale, Box and Block Test and Wolf Motor Assessment Scale were significantly improved from baseline to six weeks (p<0.05). Conclusion: This study concluded that the hemiplegic stroke survivors who received additional Virtual Reality training using Xbox Kinect showed significant improvement in Gross motor Function, Gross Manual Dexterity and Functional Abilities of the Upper Limb.